New species of Oculatella (Synechococcales, Cyanobacteria) from terrestrial habitats of Ukraine - Vinogradova, O.M.; Mikhailyuk, T.I.; Glaser, K.; Holzinger, A.; Karsten, U. (Український ботанічний журнал, 2017)
Here we describe two new species of Oculatella Zammit, Billi & Albertano from terrestrial habitats of Ukraine: O. ucrainica sp. nov. and O. kazantipica sp. nov. The strains were isolated from biological crusts collected at the Sea of Azov conqina beach, and both clay slopes and chalk outcrops in the Kharkiv Region. Five strains evaluated in this study phenotypically and phylogenetically differed both among each other and from other species of this genus. On the phylogenetic tree based on 16S rRNA gene sequence comparison, original strains joined already known species of Oculatella forming isolated lineages, one of which joined the group of drought-resistant terrestrial species (O. ucrainica), while another (O. kazantipica) grouped together with terrestrial O. neakameniensis Kováčik et Johansen and aquatic O. hafneriensis Kováčik et Johansen. The phylogeny based on the 16S rRNA gene concatenated with the 16S-23S ITS region, as well as secondary structures of the most informative helices of the 16S-23S ITS confirmed new species designation. Filaments of O. ucrainica are narrower (1.5–3.0 μm), and trichomes are wider (1.3–2.7 μm) comparing to O. kazantipica (its filaments are 1.3–7.5 μm wide, trichomes 1.1–1.7 μm wide). The new species also differ from one another in sheath morphogenesis, appearence of trichomes, and cell length. Oculatella ucrainica morphologically and phylogenetically is close to desert species O. coburnii Pietrasiak et Johansen, differing in the higher degree of sheath formation, wider trichomes, apical cells without irregular outgrowth, and by composition and secondary structure of 16S-23S ITS region. O. kazantipica is similar to O. hafneriensis and O. neakameniensis, from which it differs in more abundant sheath, false branching, granulations at cross walls, longer intercalary cells, and by composition and secondary structure of its 16S-23S ITS region.